INOVASI SUPERVISI PENDIDIKAN ISLAM DI ERA TEKNOLOGI DIGITAL - Awaluddin, Asep (Universitas Nahdlatul Ulama Surakarta, 2025)
The development of technology has an impact on all aspects of human life, including education. Apart from the era of the industrial revolution 4.0, the era of society 5.0 has emerged. This requires education to face it. Islamic education as part of education continues to strive in contemporary life to be able to face the various challenges that arise. For that, how to formulate supervision of Islamic education in the era of society 5.0. This study uses a mixed method, namely field studies and literature by exploring data based on discussions that are part of data collection techniques. This discussion examines the era of society 5.0 and the challenges of contemporary Islamic education. The results of this study: 1) The era of society 5.0 is an era that must be faced, 2) The challenges of contemporary Islamic education must be able to solve various problems through critical and analytical thinking skills, creative and innovative in various aspects of life, 3) Efforts that must be made by Islamic education in facing the challenges of the times